P048 Motor mapping by transcranial magnetic stimulation reveals persistent ipsilateral corticospinal connections in the epileptic hemisphere in patients with intractable focal epilepsy. Issue 3 (March 2017) - Kaye, H.L.; Gersner, R.; Pascual-Leone, A.; Boes, A.; Peters, J.; Rotenberg, A.
Abstract : Introduction & objectives: While corticospinal connections are overwhelmingly contralateral in children after the toddler years, ipsilateral corticospinal connections may persist in older children and adults particularly for the foot and proximal muscles. Here we test whether such preserved ipsilateral corticospinal connectivity occurs with bias toward either the affected or unaffected hemisphere in focal epilepsy. We reviewed the anatomical findings for the tibialis anterior (TA) representation in patients with intractable focal epilepsy without gross motor cortex abnormality, who underwent motor mapping by navigated transcranial magnetic stimulation (TMS) as part of epilepsy surgery evaluation. Patients & methods: Children with epilepsy from a range of causes were entered into the study if they: (1) had focal, unilateral seizures, (2) undergone TMS mapping of motor cortical output to the TA bilaterally with a figure-of-eight coil, (3) have no evidence of MRI lesion in the region of the motor cortex or corticospinal tract, and (4) been found to have preserved ipsilateral TA representation in only one hemisphere. Of the 106 patients (ages 10 mo-27 y) who had nTMS for presurgical planning, 42 had motor mapping of both the left and right TA muscles. 20 of 44 patients had ipsilateral TA motor representation in both hemispheres, and 14 patients (age 13.2 y ± 5.2) met the predefined criteria for the analysis, with ipsilateral TA representation in only one hemisphere (Fig. 1 ). Results: In every patient with focal epilepsy that had a unilateral ipsilateral TA representation it was on the affected, epileptic hemisphere (14 of 14, 100%; p < 0.01). Conclusions: Our findings suggest a pathologically-preserved immature motor lateralization in pediatric patients with focal epilepsy. This may be due to sustained abnormal electrical activity that alters normal corticospinal pathway maturation and maintains ipsilateral motor representation.